ANALISIS BIBLIOMETRIK PERKEMBANGAN PENELITIAN BIDANG ILMU GEOGRAFI - Istiana, Purwani (BACA: Jurnal Dokumentasi dan Informasi, 2024)
ABSTRACT Research data and publications that have been carried out can be essential data in bibliometric analysis to determine the development of an institution’s publication profile. This study aims to analyze the research publication by geography lecturers at Gajah Mada University, indexed by Scopus in 1991-2021. This analysis includes the distribution of publications, types, sources of publication documents, the most prolific authors, collaborating affiliations, and trending publication themes. The research method used was a quantitative descriptive method by conducting a bibliometric analysis of the publication of the lecturers of the Faculty of Geography, Gadjah Mada University, indexed by Scopus. The findings showed that (a) there were 801 total publications, with an increase in the number of publications since 2014 (8 documents) and peaking in 2020 (218 documents); (b) the most published documents were conference papers (58.67%); (c) Most source documents from the IOP Conference Series Earth and Environmental Science; (d) Most lecturers collaborated with the Laboratoire de Géographie Physique; (e) The most productive lecturer was Marfai, M.A.; and (f) Research trends themed Worldview 2, Mapping, Remote Sensing, GIS, and Tsunami. It is necessary to increase the number of publications in academic journal, due to the publications are dominated in conference papers at present. ABSTRAK Data penelitian dan publikasi yang sudah pernah dilakukan dapat menjadi data penting dalam analisis bibliometrik untuk mengetahui perkembangan profil publikasi suatu institusi. Penelitian ini bertujuan menganalisis publikasi hasil penelitian dosen geografi Universitas Gajah Mada yang terindeks Scopus tahun 1991-2021. Analisis ini meliputi sebaran publikasi, tipe dan sumber dokumen publikasi, penulis yang paling produktif, afiliasi yang berkolaborasi, dan tren tema publikasinya. Metode penelitian menggunakan metode deskriptif kuantitatif dengan melakukan analisis bibliometrik terhadap data publikasi dosen Fakultas Geografi, Universitas Gadjah Mada yang terindeks Scopus. Hasil penelitian menunjukkan bahwa (a) total publikasi ada 801, dengan peningkatan jumlah publikasi sejak tahun 2014 (8 dokumen) dan puncaknya pada 2020 (218 dokumen); (b) dokumen publikasi terbanyak dalam conference paper (58,67%); (c) Sumber dokumen terbanyak dari Iop Conference Series Earth and Environmental Science; (d) Kolaborasi dosen terbanyak dengan Laboratoire de Géographie Physique; (e) Dosen paling produktif adalah Marfai, M.A.; dan (f) Tren penelitian bertema Worldview-2, Mapping, Remote Sensing, GIS, dan Tsunami. Perlu peningkatan jumlah publikasi dalam bentuk jurnal, karena pada saat ini publikasi masih didominasi dalam bentuk conference paper.